2013
DOI: 10.1017/s0007114513000664
|View full text |Cite
|
Sign up to set email alerts
|

Release of EPA and DHA from salmon oil – a comparison ofin vitrodigestion with human and porcine gastrointestinal enzymes

Abstract: In the present study, we hypothesised whether in vitro digestion of salmon oil would release different amounts of PUFA depending on the origin of the lipolytic enzymes used. For this purpose, in vitro digestion of salmon oil (SO) was performed using human duodenal juice (HDJ) or a commercial enzyme preparation consisting of porcine pancreatin and bile (PB). The lipolytic effect was determined by measuring the release of fatty acids (FA) using solid-phase extraction and GC -flame ionisation detection, withdrawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…The same observation was made for DHA, with a higher release in the human model compared to the porcine models I and II (230% increase during digestion, compared to 490% and 680%, respectively). This supports the findings of Aarak et al 51 that there are differences in the release of EPA and DHA when using human versus porcine digestive enzymes. According to above, there could be a link between the release of free EPA/ DHA and the extent of lipid oxidation in the duodenal step.…”
Section: Lipolysis During In Vitro Digestion Of Cod Liver Oilsupporting
confidence: 91%
“…The same observation was made for DHA, with a higher release in the human model compared to the porcine models I and II (230% increase during digestion, compared to 490% and 680%, respectively). This supports the findings of Aarak et al 51 that there are differences in the release of EPA and DHA when using human versus porcine digestive enzymes. According to above, there could be a link between the release of free EPA/ DHA and the extent of lipid oxidation in the duodenal step.…”
Section: Lipolysis During In Vitro Digestion Of Cod Liver Oilsupporting
confidence: 91%
“…Therefore, the higher polyunsaturation of FAs located in sn-1,3 and the double bond close to the carboxyl group inhibit the TAG hydrolysis activity of lipase, resulting in lower digestion rates of microalgal oil and fish oil compared to that of soybean oil. Aarak et al [26] analyzed the profile of released FAs after in vitro digestion of salmon oil with human duodenal juice and a commercial enzyme preparation (porcine pancreatin and bile), and reported that the concentration of linoleic acid was the highest, followed by EPA and DHA (p < 0.05).…”
Section: In Vitro Digestion Of the Oilsmentioning
confidence: 99%
“…The enzymes are collected from human subjects, though a number of studies consider that it is possible to replace human pepsin, pancreatic lipase and co-lipase with porcine enzymes (Hur et al 2011 ). Aarak et al 2013 compared in vitro models using human and porcine intestinal enzymes applied to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) release from salmon, using only a duodenal digestion step. Results show that the human lipolytic enzyme system produces a comparatively higher release of EPA and DHA.…”
Section: Digestion Conditionsmentioning
confidence: 99%